2017
DOI: 10.1097/iae.0000000000001263
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Internal Limiting Membrane Peeling on Idiopathic Epiretinal Membrane Surgery, With a Review of the Literature

Abstract: The rate of recurrent ERM and need for repeat ERM surgery is lower in eyes where the ILM is removed with the ERM, whereas BCVA and CMT were similar with or without ILM removal. Complete ILM removal around the macula should be considered for the treatment of eyes with idiopathic ERMs to reduce the incidence of ERM recurrences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
1
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(52 citation statements)
references
References 20 publications
1
43
1
6
Order By: Relevance
“…The heterogeneity of a difference in CMT at the final follow-up was effectively decreased after excluding the study,5 I 2 changed from 55% to 0%. The heterogeneity of the difference in ERM recurrence was effectively decreased after excluding the study,26 30 I 2 changed from 43% to 0%.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The heterogeneity of a difference in CMT at the final follow-up was effectively decreased after excluding the study,5 I 2 changed from 55% to 0%. The heterogeneity of the difference in ERM recurrence was effectively decreased after excluding the study,26 30 I 2 changed from 43% to 0%.…”
Section: Resultsmentioning
confidence: 97%
“…Ten included studies were retrospective cohort studies,5 7 20–25 29 30 one was prospective cohort study26 and two were RCTs 27 28…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ILM removal has been shown to be beneficial in terms of final visual outcome and reduction of ERM recurrence [6][7][8][9]. Gandorfer et al [22] demonstrated that the ERM removal alone did not lead to a complete separation of the fibrocellular tissue from the macula.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, ERM peeling is the gold standard technique in macular pucker surgery leading to good visual and anatomical outcomes in the majority of cases. Nevertheless, visual acuity improvement is rarely complete, and an ERM recurrence rate of 21% has been reported [8][9][10]. The unsatisfactory improvement of visual acuity and the recurrence of ERM seem to be correlated with an incomplete removal of the ERM [11,12].…”
Section: Introductionmentioning
confidence: 99%